Commercial contracts : a practical guide to deals contracts, agreements and promises - Thorpe, C. P. (Woodhead, 1996)
This book aims to explain the principles of contract law for the businessman, and to put those principles into their commercial context. Anyone involved in commercial transactions needs at least a basic understanding of the principles of contract law - the legal framework for all commercial activity. A lack of such a basic understanding at best results in a business which is less competitive and ultimately less profitable than it should be, and at worst can have expensive and sometimes disastrous commercial consequences.